Valorization of Tuna (Thunnus sp.) Viscera by-Product Into Hydrolysates and Optimizing Bromelain-Mediated Hydrolysis for Functional Applications - Rohmah, Arina Maulidatur; Janah, Diana Roudhotul; Pramono, Heru; Pujiastuti, Dwi Yuli (JFMR-Journal of Fisheries and Marine Research, 2026)
Tuna (Thunnus sp.) viscera by-product, representing 12–18% (w/w) of total fish biomass, is an underutilized resource that poses environmental challenges if not well managed. However, its high protein content offers significant potential for the production of bioactive protein hydrolysates (FPH). This study aimed to evaluate the impact of bromelain-mediated enzymatic hydrolysis duration (0, 1, 3, and 6 hours) at 54°C on the chemical characteristics and antibacterial efficacy of the resulting hydrolysates against Escherichia coli and Staphylococcus aureus. Results indicated that while the 3-hour hydrolysis treatment yielded the highest protein content (85.109%), the 6-hour treatment provided the highest degree of hydrolysis (17.885%) and yield (9.113%). Notably, while initial screenings (Minimum Inhibition Concentration and Minimum Bactericidal Concentration assays) at 64–256 mg/mL shown no inhibitory activity, the 6-hour hydrolysate at a higher concentration of 1000 mg/mL demonstrated bacteriostatic activity. Using the disc diffusion method, this treatment produced inhibition zones of 1.735 mm against Staphylococcus aureus and 1.330 mm against Escherichia coli. These findings suggest that while tuna viscera protein hydrolysates possess antibacterial potential, their efficacy is highly dependent on both hydrolysis duration and concentration, providing a foundation for future valorization of fish processing by-products.